The Effect of Kahoot and YouTube as Teaching Media on Plot-Based Narrative Writing Skill of AEC Siantar Students: English - Sanggam Siahaan; Theodora Evita Lumbanraja; Rika Budiarti; Cinta Yulistra Tindaon (Prodi Tadris Bahasa Inggris, 2025)
The aim of this research is to ascertain the relative significance of Kahoot versus YouTube as teaching media on students' plot-based narrative writing skills. Employing quantitative methodology, this research utilized quasi-experimental design featuring pre-tests and post-tests to examine the noteworthy enhancement of students' writing abilities. The population of research focused on the students of AEC Siantar. Researchers thoughtfully selecting two Soft Start classes to serve as experimental and control groups. The choice to implement purposive sampling was primarily motivated by the importance of maintaining a balanced composition and comparable average abilities within both classes. Through analysis of hypothesis testing, researchers reached a compelling conclusion: the t-test value exceeded t-table value (5.204 > 1.706). As a result, alternative hypothesis (Ha) was accepted while null hypothesis (H0) was rejected. Consequently, researchers confidently affirmed that the use of Kahoot and YouTube has significant effect on plot-based narrative writing skills of AEC Siantar students, with Kahoot emerging as more effective teaching media